Purification and characterization of myotoxin IV, a phospholipase A2 variant, from Bothrops asper snake venom - Díaz Oreiro, Cecilia (1995)
A basic myotoxic protein was purified from Bothrops asper venom. Like other basic Bothrops myotoxins, myotoxin IV induces acute muscle damage after intramuscular injection in mice and disrupts negatively charged liposomes but not positively charged ones. Furthermore, this protein exerts a weak anticoagulant effect only at concentrations of 40 μg/ml or higher, and is devoid of phospholipase A2 activity. Rabbit polyclonal antibodies to B. asper myotoxin II, a related lysine-49 isoform, cross-react strongly with myotoxin IV by enzyme immunoassay, indicating a high degree of antigenic similarity between these two proteins. The fact that both toxins have similar amino acid compositions and amino-terminal sequences, including leucine-5 and glutamine-11, 2 amino acid residues conserved in all lysine-49 phospholipase A2 variants purified, strongly suggests that B. asper myotoxin IV is a lysine-49 phospholipase A2.